Does managerial ability matter for corporate climate change disclosures?. (21st March 2022) - Daradkeh, Hussein; Shams, Syed; Bose, Sudipta; Gunasekarage, Abeyratna
Abstract: Research Question/Issue: This study examines the association between managerial ability and the extent of firm‐level climate change disclosures and the moderating role of corporate governance in this association. Research Findings/Insights: Results based on a sample of 2298 firm‐year observations from the United States (US) from 2005 to 2019 suggest that firms with more capable managers tend to make more climate change disclosures. This significant positive association is weakened when firms suffer from weak corporate governance. These findings remain robust after addressing omitted time‐invariant variable bias, observable heterogeneity bias, sample selection bias, and reverse causality and when using alternative climate change disclosure proxies. Further analysis shows that climate change disclosures have a mediating role in the association between managerial ability and firm valuation. Theoretical/Academic Implications: Given the growing importance of integrating climate change‐related information into a firm's operations and the pressure exerted by various stakeholders, understanding the drivers of climate change disclosures has emerged as an important area of research in the accounting and finance literature. To the best of our knowledge, this is the first study to examine any link between managerial ability and climate change disclosures. Practitioner/Policy Implications: Considering the recent pressure imposed on companies by regulatory authorities for more climate change disclosures, our study's findings have important implications for regulators, policy makers, investors, financial analysts, researchers, and firms.